Nikah Sirri Menurut Hukum Islam Dan Hukum Positif - Zakaria, Endang; Saad, Muhammad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
Islamic law defines marriage as an absolute obligation to follow Allah's command and carry it out as worship and represents a very strong bond. In the context of unregistered marriage, it can be defined as “a form of marriage based on religious law or custom, as well as one that is not announced to a crowd and is not registered with the marriage registry”. This paper discusses literacy in Islamic law and positive law on unregistered marriages. Positive law studies on  unregistered  marriages   are  carried  out  on  the   essence  of  the Law of the Republic of Indonesia and Government Regulations. According   to  Indonesian   law,   sirri   marriage   is a  marriage   that is not based on the principle of legality. In Islam, the study of unregistered   marriage   was   based   on   Qur’an   and   hadith.   This means that it is not legally binding. A marriage that is in accordance   with   the  pillars  and   conditions   of   marriage   is valid  under  Islamic law, as are   marriages   performed   in   sirri marriages, as defined in Indonesian law.